Dendronized Silver Nanoparticles as Bacterial Membrane Permeabilizers and Their Interactions With P. aeruginosa Lipopolysaccharides, Lysozymes, and Phage-Derived Endolysins - Ciepluch, Karol; Skrzyniarz, Kinga; Barrios-Gumiel, Andrea; Quintana, Sara; Sánchez-Nieves, Javier; de la Mata, F. Javier; Maciejewska, Barbara; Drulis-Kawa, Zuzanna; Arabski, Michał (Frontiers in Microbiology, 2019)
Antimicrobial proteins, like lysozymes produced by animals or bacteriophage lysins, enable the degradation of bacterial peptidoglycan (PG) and, consequently, lead to bacterial cell lysis. However, the activity of those enzymes is not satisfactory against gram-negative bacteria because of the presence of an outer membrane (OM) barrier. Lytic enzymes can therefore be combined with membrane-disrupting agents, such as dendritic silver nanoparticles. Nevertheless, a lipopolysaccharide (LPS), especially the smooth type, could be the main hindrance for highly charged nanoparticles to get direct access to the bacterial OM and to help lytic enzymes to reach their target PG. Herein, we have investigated the interactions of PEGylated carbosilane dendritic nanoparticles with P. aeruginosa 010 LPS in the presence of lysozymes and KP27 endolysin to find out the main aspects of the OM destabilization process. Our results showed that PEGylated dendronized AgNPs overcame the LPS barrier and enhanced the antibacterial effect of endolysin more efficiently than unPEGylated nanoparticles.